"I'm in a very good frame of mind": a qualitative exploration of the experience of standing frame use in people with progressive multiple sclerosis. Issue 10 (28th October 2020) - Dennett, Rachel; Hendrie, Wendy; Jarrett, Louise; Creanor, Siobhan; Barton, Andrew; Hawton, Annie; Freeman, Jennifer A
Abstract : Objectives: The study aim was to explore the experiences of people with progressive multiple sclerosis (MS) and their standing assistants during their participation in Standing Up in Multiple Sclerosis, a randomised controlled trial (RCT) of a home-based, self-managed standing frame programme. Design: A qualitative approach, using audio diary methodology was used to collect data contemporaneously. Diary data were transcribed verbatim and analysed using thematic analysis. Setting: Participants were recruited from eight healthcare organisations in two regions of the UK. The intervention was home-based. Participants: As part of the RCT, 140 participants were randomly allocated to either usual care or usual care plus a standing frame programme. Using a sampling matrix 12 people with progressive MS (6 female, aged 35–71 years, Expanded Disability Status Scale 6.5–8.0) and 8 standing assistants (4 female) kept audio diaries of their experiences. Intervention: The standing frame programme involved two face-to-face home-based physiotherapy sessions to set up the standing frame programme, supplemented by educational material designed to optimise self-efficacy. Participants were encouraged to stand for at least 30 min, three times a week for the 36-week study period. Results: Four main themes were identified: "Feeling like the old me"; 'Noticing a difference'; "I want to do it right" and "You have a good day, you have a bad day". Conclusions: Supported standing helped people with progressive MS feel more like their old selves and provided a sense of normality and enjoyment. People noticed improvements in physical and psychological symptoms, which were often associated with increased participation in activities they valued. Provision of support from a physiotherapist and recognition of the variable nature of the condition were highlighted as factors to consider when establishing a standing programme. Trial registration number: ISRCTN69614598 .